Evaluation and Comparison of Newly Developed Phosphoric Acid Gel (Exir) with Two Different Common Gels in Iran - Hamideh Mohammadipour; majid akbari; Hossein Bagheri; Mohammadtaghi Malekmohammadi; elnaz karimian; Salehe Sekandari (Mashhad University of Medical Sciences, 2021)
Introduction: Different surface treatments were preposed to prepare the tooth structure for resin composite bonding. One of the most common preparation is using of phosphoric acid etching. This study conducted to determine the etching effectiveness of a new formulated acid etchant (Exir) and compared it with two commercial products. Methods: To determine the physical properties, the viscosity and shelf life were evaluated by a viscometer and a centrifuge over the time, respectively. SEM micrographs were uesd to show the geometry of bovine enamel and dentin surfaces which were treated by three etchants. The µSBS of composite to treated dental tissues was also investigated. Data were analyzed by ANOVA and Tukey test (α=0.05). Results: Exir etchant showed the lower viscosity compared with two other gels and two-phase separation did not significantly increase during suggested period. The SEM images of enamel samples treated with Exir etchant showed regular etching patterns and less remnant in comparison with other groups. The SEM mages of dentin samples treated with Exir etchant, unlike others, showed wide open dentin tubules with clear exposed collagen fibers. Enamel and dentin µSBS were 30.08±6.79 and 7.29±1.27 for Exir etchant, 23.31±6.64 and 8.49±3.61 for Morva Etch and 23.22±7.05 and 6.16±1.68 for Ultra-Etch, respectivley. The µSBS values ​​for enamel was significantly higher in Exir treated group (P=0.017), while there was no significant difference in dentin µSBS values among three tested etchants (P=0.07). Conclusion: The results of this study showed Exir etchant can provide acceptable results used on dentin and enamel substrates.